External school evaluation : teachers’ perspectives : two case studies from Northern Portugal - Seabra, Filipa (2015)
The external evaluation of non-higher education schools in Portugal has been developed by the General Inspectorate of Education since 2006. A first cycle of evaluation was completed, covering all educational units in continental Portugal up to 2011. The model of evaluation has since been subject to alterations, and a second cycle of evaluation is now coming to an end. The current model of evaluation is based on documental analysis, analysis of students’ results, and panel interviews with a variety of representatives of the school community, and addresses three domains: results, provision of educational service and management. This paper is part of an ongoing research project, developed by 6 universities and supported by the Portuguese Foundation for Science and Technology (PTDC/CPE-CED/116674/2010) which intends to analyse the impacts and effects this process of external evaluation has had on Portuguese schools. This project includes a variety of perspectives and methodologies. In particular, we will focus on two case studies undertaken in two schools from the northern region of Portugal, and more specifically on the perspectives expressed by the teachers of those schools. These particular schools were chosen because they have been evaluated twice and represent different educational levels (basic and secondary), contexts and results. These case studies included the analysis of documental data, interviews to key informants and a questionnaire directed to teachers (n = 141) – the latter will be the main focus of this paper. Teachers are essential elements of the school community when considering the impacts of external evaluation, as any changes directed at teaching practices, student evaluation, among others are only possible through their direct action and implication. Therefore, their perceptions on the process and its impacts are crucial to the understanding of what does and does not change in schools as a consequence of external evaluation. Although teachers’ opinions are not homogenous and each school reveals a number of differences when it comes to teachers’ perceptions of School Evaluation, it was possible to stress some areas as the most and as the least consensual. Teachers in both schools agree External School Evaluation (ESE) is useful for the identification of the schools’ strengths and weaknesses, values students’ external evaluation results, imposes a model for schools internal evaluation (and in fact contributes to the very existence of internal evaluation practices), and contributes to schools improvement. However teachers in both schools do not believe ESE contributes to teachers’ autonomy produces changes in how curriculum is managed, or leads to innovative teaching practices. These results point to a greater emphasis on change at the levels of school management, self-evaluation and particularly internal evaluation, but little impact on the teaching practices. We believe the classroom is at the core of school practices and teaching processes are essential to any measure of school quality and to their impacts on student learning.